ChemInform Abstract: Enantio‐ and Regioselective Iridium‐Catalyzed Allylic Esterification. Issue 34 (26th August 2014) - Qu, Jianping; Rossberg, Lydia; Helmchen, Guenter
Abstract A synthesis of a broad range of aliphatic and aromatic substituted chiral allyl esters with high enantiomeric excess from allyl phosphates is presented.